ANALISIS PENGELOLAAN BIAYA DAN LABA PADA UMKM KONVEKSI DI MARKETPLACE: STUDI PADA MM KIDSSTORE OFFICIAL DI SHOPEE - Nafisah, Alfi Ilmiyatun; Adinugraha, Hendri Hermawan; Gunawan, Ade (AL-IQTISHAD : Jurnal Perbankan Syariah dan Ekonomi Islam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the national economy, especially in the high-demand convection sector. With the development of digital technology, many MSMEs utilize marketplaces such as Shopee to expand market reach. This study aims to analyze cost and profit management strategies in marketplace-based convection MSMEs, with a case study of MM Kidsstore Official, a children's clothing manufacturer operating on Shopee. The method used is a qualitative approach through observation and interviews with business owners. The results showed that cost management is still done manually and simply, only including recording raw materials and sales. Pricing is done intuitively without clear cost analysis and profit targets, resulting in inconsistent profitability. Utilizing the marketplace does increase sales, but it also increases costs such as advertising, commissions, and postage subsidies. If not managed properly, this can reduce business profits. The study recommends applying the full costing method and cost-volume-profit (CVP) analysis for more systematic financial planning. The findings are expected to serve as a reference for MSMEs in developing adaptive and sustainable financial strategies in the digital era.